FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN PERAWAT DALAM PENUGASAN COVID-19 - Elfrida Juniartha (2022)
COVID-19 is still ongoing and there are still predictions of an increase in cases in the future, so the incidence of a surge in COVID-19 must be anticipated, especially in the health service sector, which is nurses as one of the health workers in handling with the COVID-19. This study aims to determine the factors related to the preparedness of nurses in RSUP dr. Sitanala during the COVID-19. This study used a cross-sectional with an accidental sampling totaling 131 nurses. The research instrument used is the Nurses' Preparedness to Response to COVID-19 Questionnaire which has been tested for validity and reliability. Based on the results of statistical tests, it is known that the factors related to the preparedness of nurses in the COVID-19 include the length of work (p = 0.005), COVID-19 training (p = 0.037), sources of knowledge and skills (p = 0.000), experience in previous outbreaks (p=0.022). Nurses are expected to participate in training and gaining more sources of knowledge and skills to form preparedness.